Triazolyl emofs filled ferrocene derivative energetic composite burning rate catalyst
By filling the nanopores of triazole-based EMOFs with ferrocene derivatives, the problems of migration and uneven distribution of ferrocene catalysts were solved, achieving efficient combustion catalysis and energy enhancement.
Patent Information
- Application Number
- CN202410735015.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-06-07
AI Technical Summary
Existing ferrocene-based combustion rate catalysts are prone to volatilization and sublimation in solid propellants, resulting in uneven distribution, reduced combustion stability and service life, and migration issues that endanger equipment and safety.
Ferrocene derivatives are filled into the nanopores of triazole-based EMOFs. By utilizing the high energy density of EMOFs and the confinement effect of nanopores, a triazole-based EMOF-filled ferrocene derivative energetic composite combustion rate catalyst is formed, which enhances catalytic performance and reduces migration.
It significantly improves the combustion efficiency of the catalyst and the energy level of the solid propellant, reduces the migration of ferrocene-based combustion rate catalysts, and improves combustion stability and safety.
Smart Images

Figure CN118619796B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid propellant technology, specifically relating to a series of composite combustion rate catalysts filled with ferrocene derivatives using triazole-based energetic metal-organic framework materials. Background Technology
[0002] Solid propellants are special energetic materials that provide power for missiles, rockets, and spacecraft. They are a crucial component of energetic materials, primarily composed of binders, oxidizers, combustion rate catalysts, plasticizers, stabilizers, antioxidants, and various functional additives. They are broadly classified into double-base propellants and composite propellants, and have wide applications in tactical missiles, aerospace, and civilian fields. The development status of solid propellants reflects a country's defense industry level, as their combustion directly affects the performance of aero-rocket. Through long-term research, solid propellants have developed towards high energy, high specific impulse, and low signal characteristics. Ammonium perchlorate (AP), a strong oxidizer, is a common energetic component in solid propellants, especially in double-base propellants and their modified forms. Because AP generally constitutes a large proportion, its combustion rate, thermal decomposition peak temperature, and heat release during decomposition significantly influence the combustion of solid propellants. Burning rate catalysts are functional materials that regulate the combustion characteristics of solid propellants. Extensive practical research has demonstrated that adding a small amount of catalyst not only increases the burning rate and reduces the pressure index of the propellant, but also lowers the burning rate temperature sensitivity coefficient within a certain temperature range. The amount of burning rate catalyst added is generally 1 wt.% to 5 wt.% of the total mass fraction of the solid propellant, but it plays a crucial role as an indispensable component. Common burning rate catalysts in solid propellants include transition metal oxides, transition metal fluorides, ferrocene and its derivatives, organometallic compounds, and nano-burning rate catalysts. Among these, ferrocene-based burning rate catalysts are widely used due to their excellent catalytic activity and good compatibility in composite solid propellants.
[0003] In 1951, chemists Kealy TJ and Pauson PL first published a compound with a unique sandwich structure in Nature, later named ferrocene. Its discovery greatly promoted the development of organometallic chemistry. From the 1960s onwards, domestic and international research focused on the development of ferrocene compounds. Studies showed that these compounds decompose at high temperatures to produce iron oxide (Fe₂O₃) with excellent catalytic activity, significantly improving the combustion characteristics of propellants. Therefore, they are often used as combustion rate catalysts in propellants. Currently, commercially available ferrocene combustion catalysts mainly include 2,2-bis(ethylferrocene)propane (Cat), n-octylferrocene (NOF), n-butylferrocene (NBF), and tert-butylferrocene (TBF). While the addition of these commercially available ferrocene-based combustion rate catalysts can significantly improve the combustion performance of solid propellants, there are still many problems to be solved in practical applications. For example, these compounds are prone to volatilization and sublimation, and migration occurs in solid propellants. These problems can lead to uneven distribution of these compounds in solid propellants and separation between the propellant grain and the liner, reducing the combustion stability and service life of solid propellants. This can easily damage engine equipment and the environment, and may even lead to accidents and endanger personal safety.
[0004] Metal-organic frameworks (MOFs) are porous functional materials with a periodic network structure composed of metal centers and organic ligands. Compared to traditional porous materials, MOFs offer significant advantages, including a large specific surface area, abundant pore structure, high porosity, and highly dispersed metal centers. Furthermore, their structure and function can be diversified. Both the metal centers and organic ligands composing MOFs are diverse, and different properties can be obtained by selecting different metal ions and ligands. Moreover, MOFs possessing multiple metal centers or organic ligands can be synthesized to achieve wide applications in various fields. MOFs not only exhibit excellent designability in terms of performance but also have relatively simple synthesis processes and low production costs, making them widely applicable in gas storage (hydrogen storage), gas separation, energy storage, and catalysis.
[0005] Energetic metal-organic frameworks (EMOFs) are framework materials with specific spatial structures formed by the self-assembly of nitrogen-rich energetic ligands and metal ions through different coordination mechanisms. They possess advantages such as high energy density, low sensitivity, high decomposition temperature, tunable structure, and environmentally friendly decomposition products, thus attracting widespread attention from energetic materials researchers. Traditional metal oxide catalysts lack energetic groups, resulting in some energy loss in the propellant. To provide energy while maintaining good catalytic activity, energetic combustion catalysts have received widespread attention. As combustion catalysts, they exhibit higher energy levels and higher combustion efficiency, improving the overall energy level of solid propellants compared to traditional combustion rate catalysts, demonstrating excellent high-energy and high-efficiency catalytic prospects. Li Jinsong et al. synthesized Cu using 4,5-bis(1-hydroxytetrazole-5-yl)-1,2,3-triazole ligands. II and Cd II Energetic metal-organic frameworks (EMOFs) have more complex three-dimensional connection modes, which can further improve structural stability and enhance the energy characteristics of EMOFs. DSC evaluation revealed that they exhibit excellent catalytic effects on the thermal decomposition of azophosphorus compounds (APs), reducing the peak decomposition temperature of AP from 704.0 K to 613.6 K and narrowing the decomposition temperature range from 451 K to 320 K (Li J, Jin Z, Jin B, et al. Synthesis of CuII and CdII metal–organic frameworks based on 4,5-bis(1-hydroxytetrazol-5-yl)-1,2,3-triazole and their effects as the catalyst in ammonium perchloratethermal decomposition[J].Inorganic Chemistry,2022,61(44):17485-17493.). CN115582145A discloses a ZIF-67 filled ferrocene derivative nanocomposite combustion rate catalyst, and CN115739185A discloses a ZIF-8 composite ferrocene nanocomposite combustion rate catalyst. These two patents utilize the binding effect of MOF nanoscale channels to stably confine ferrocene derivatives in the channels, greatly reducing the migration of ferrocene-based combustion rate catalysts and effectively solving the problem of easy migration of ferrocene-based combustion rate catalysts. Summary of the Invention
[0006] The purpose of this invention is to provide a series of triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalysts that are simple to prepare, can be mass-produced, have good catalytic activity, and can greatly reduce the migration of ferrocene-based combustion rate catalysts during long-term storage of solid propellants. This material utilizes the properties of EMOFs to fill ferrocene derivatives into their nanopores during the synthesis of Mn-EMOFs, thereby reducing the migration problem of ferrocene-based combustion rate catalysts. Simultaneously, it leverages the high energy density of EMOFs to improve the overall energy level of solid propellants. Furthermore, during the combustion and decomposition of AP, the synergistic catalytic effect of ferrocene derivatives and Mn-EMOFs enhances the combustion catalytic effect on the thermal decomposition of AP.
[0007] To achieve the above objectives, the triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalyst provided by the present invention is a ferrocene derivative-filled nanopore of an energetic metal-organic framework material with manganese as the metal center and triazole compounds as organic ligands.
[0008] The above-mentioned triazole compounds are selected from any one of 1H-1,2,4-triazole (Trtz), 3-amino-1,2,4-triazole (ATrtz), and 3,5-diamino-1,2,4-triazole (DAT).
[0009] The ferrocene derivatives mentioned above are selected from any one of catoxine (Cat), n-butylferrocene (NBF), ethylferrocene (EF), and 1,1'-diethylferrocene (DEF).
[0010] In the above-mentioned energetic composite combustion rate catalyst, the mass ratio of ferrocene derivative to energetic metal-organic framework material is 0.10 to 0.16:1.
[0011] The preparation method of the triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalyst of the present invention is as follows: a triazole compound and a ferrocene derivative are dissolved in a mixed solvent of methanol and acetone to obtain solution A; manganese perchlorate is dissolved in a mixed solvent of methanol and acetone to obtain solution B; then, under stirring conditions, solution B is added dropwise to solution A, and the pH is adjusted to 7-8 with triethylamine. The reaction is stirred at room temperature for 8-12 hours. The resulting precipitate is washed by centrifugation with anhydrous diethyl ether until colorless, and then dried under vacuum to obtain the triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalyst.
[0012] In the above preparation method, the preferred molar ratio of manganese perchlorate to triazole compounds and ferrocene derivatives is 1:3 to 6:3 to 6.
[0013] In the above preparation method, the volume ratio of methanol to acetone in the mixed solvent is preferably 0.5 to 1.5:1.
[0014] In the above preparation method, the centrifugation speed is preferably 9000-10000 rpm and the centrifugation time is 3-4 min.
[0015] In the above preparation method, the vacuum drying temperature is preferably 60-70°C and the time is 6-8 hours.
[0016] The beneficial effects of this invention are as follows:
[0017] 1. This invention fills ferrocene derivatives into the nanopores of EMOFs, utilizing the confinement effect of these nanopores to stably confine the ferrocene derivatives within the pores. Furthermore, the synthesized EMOFs utilize high-nitrogen ligands, resulting in a composite burning rate catalyst with high energy levels, thereby improving the overall energy level of solid propellants. Simultaneously, the catalytic properties of the ferrocene derivatives and EMOFs are complementary, generating a strong "synergistic effect" and significantly enhancing their catalytic performance. Moreover, the stable confinement of the ferrocene derivatives within the pores greatly reduces their migration during long-term storage of solid propellants, effectively solving the problem of easy migration in ferrocene-based burning rate catalysts.
[0018] 2. This invention combines traditional catalysts with nanomaterials to obtain a novel nanocomposite catalyst, which directly and effectively improves the migration problem of ferrocene burning rate catalysts in propellants through simple physical principles. This invention is simple to operate, has a high yield, and can be mass-produced. It can obtain low-migration ferrocene burning rate catalysts under simple processing methods, and the resulting low-migration ferrocene cumulative burning rate catalyst has a filling rate between 10 wt.% and 16 wt.%. This composite material has the advantages of low migration, large specific surface area, and good catalytic effect. Attached Figure Description
[0019] Figure 1 This is a field emission electron microscope image of the energetic composite combustion rate catalyst prepared in Example 1.
[0020] Figure 2 This is a field emission electron microscope image of the energetic composite combustion rate catalyst prepared in Example 2.
[0021] Figure 3 This is a field emission electron microscope image of the energetic composite combustion rate catalyst prepared in Example 3.
[0022] Figure 4 The results are DSC test results of the energetic composite combustion rate catalysts prepared in Examples 1-3 and the EMOFs prepared in Comparative Examples 1-3, respectively, with 5 wt.% added to AP and AP.
[0023] Figure 5The results are DSC analysis of the energetic composite combustion rate catalysts prepared in Examples 4-6 and the EMOFs prepared in Comparative Examples 1-3, with 5 wt.% added to AP and AP respectively, as well as n-butylferrocene.
[0024] Figure 6 The results are DSC test results of the energetic composite combustion rate catalysts prepared in Examples 7-9 and the EMOFs prepared in Comparative Examples 1-3, respectively, with 5 wt.% added to AP and AP.
[0025] Figure 7 The results are DSC analysis of the energetic composite combustion rate catalysts prepared in Examples 10-12 and the EMOFs prepared in Comparative Examples 1-3, respectively, with 5 wt.% added to AP and AP.
[0026] Figure 8 The results are the 24-hour isothermal thermogravimetric analysis results of the energetic composite combustion rate catalysts prepared by Katoxin and Examples 3, 6, 9, and 12.
[0027] Figure 9 These are images from the Katoxin migration test.
[0028] Figure 10 These are migration test images of the energetic composite combustion rate catalyst prepared in Example 3. Detailed Implementation
[0029] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited to these embodiments.
[0030] Example 1
[0031] 276.3 mg (4 mmol) of 1H-1,2,4-triazole and 1128.8 mg (4 mmol) of captocillin were added to 40 mL of a 1:1 mixture of methanol and acetone. The solution was dissolved by stirring at 25 °C and recorded as solution A. Then, 361.9 mg (1 mmol) of Mn(ClO4)2·6H2O was added to 20 mL of a 1:1 mixture of methanol and acetone. The solution was dissolved by stirring at 25 °C and recorded as solution B. Solution A was placed on a magnetic stirrer and stirred at 600 rpm. -1 Solution B was slowly added dropwise to solution A, and the pH of the solution was adjusted to 7-8 with triethylamine. The mixture was stirred at 25°C for 12 hours. After the reaction, the solution was washed with anhydrous diethyl ether by centrifugation at 8000 rpm for 4 minutes each time, until the supernatant was completely colorless and transparent. The brown solid precipitate was then dried in a vacuum drying oven at 70°C for 6 hours, ground, and collected to obtain the brown Mn-EMOFs-filled catoxine energetic composite combustion rate catalyst, denoted as Cat@MnTrtz. Its field emission electron microscope image is shown below. Figure 1 .
[0032] Example 2
[0033] 336.3 mg (4 mmol) of 3-amino-1,2,4-triazole and 1128.8 mg (4 mmol) of captocillin were added to 40 mL of a 1:1 mixture of methanol and acetone. The solution was dissolved by stirring at 25 °C and recorded as solution A. Then, 361.9 mg (1 mmol) of Mn(ClO4)2·6H2O was added to 20 mL of a 1:1 mixture of methanol and acetone. The solution was dissolved by stirring at 25 °C and recorded as solution B. Solution A was placed on a magnetic stirrer and stirred at 600 rpm. -1 Solution B was slowly added dropwise to solution A, and the pH of the solution was adjusted to 7-8 with triethylamine. The mixture was stirred at 25°C for 12 hours. After the reaction, the solution was washed with anhydrous diethyl ether by centrifugation at 8000 rpm for 4 minutes each time, until the supernatant was completely colorless and transparent. The brown solid precipitate was then dried in a vacuum drying oven at 70°C for 6 hours, ground, and collected to obtain the brown Mn-EMOFs-filled catoxine energetic composite combustion rate catalyst, denoted as Cat@MnATrtz. Its field emission electron microscope image is shown below. Figure 2 .
[0034] Example 3
[0035] 396.4 mg (4 mmol) of 3,5-diamino-1,2,4-triazole and 1128.8 mg (4 mmol) of captocillin were added to 40 mL of a 1:1 mixture of methanol and acetone. The solution was dissolved by stirring at 25 °C and recorded as solution A. Then, 361.9 mg (1 mmol) of Mn(ClO4)2·6H2O was added to 20 mL of a 1:1 mixture of methanol and acetone. The solution was dissolved by stirring at 25 °C and recorded as solution B. Solution A was placed on a magnetic stirrer and stirred at 600 rpm. -1 Solution B was slowly added dropwise to solution A, and the pH of the solution was adjusted to 7-8 with triethylamine. The mixture was stirred at 25°C for 12 hours. After the reaction, the solution was washed with anhydrous diethyl ether by centrifugation at 8000 rpm for 4 minutes each time, until the supernatant was completely colorless and transparent. The brown solid precipitate was then dried in a vacuum drying oven at 70°C for 6 hours, ground, and collected to obtain the brown Mn-EMOFs-filled catoxine energetic composite combustion rate catalyst, denoted as Cat@MnDAT. Its field emission electron microscope image is shown below. Figure 3 .
[0036] Example 4
[0037] In this embodiment, equimolar n-butylferrocene was used to replace catoxine in Example 1, and the other steps were the same as in Example 1, to obtain a brown Mn-EMOFs-filled n-butylferrocene energetic composite combustion rate catalyst, denoted as NBF@MnTrtz.
[0038] Example 5
[0039] In this embodiment, equimolar n-butylferrocene was used to replace catoxine in Example 2, and the other steps were the same as in Example 2, to obtain a brown Mn-EMOFs-filled n-butylferrocene energetic composite combustion rate catalyst, denoted as NBF@MnATrtz.
[0040] Example 6
[0041] In this embodiment, equimolar n-butylferrocene was used to replace catoxine in Example 3, and the other steps were the same as in Example 3, to obtain a brown Mn-EMOFs-filled n-butylferrocene energetic composite combustion rate catalyst, denoted as NBF@MnDAT.
[0042] Example 7
[0043] In this embodiment, equimolar ethyl ferrocene was used to replace catoxine in Example 1, and the other steps were the same as in Example 1, to obtain a brown Mn-EMOFs-filled n-butyl ferrocene energetic composite combustion rate catalyst, denoted as EF@MnTrtz.
[0044] Example 8
[0045] In this embodiment, equimolar ethyl ferrocene was used to replace catoxine in Example 2, and the other steps were the same as in Example 2, to obtain a brown Mn-EMOFs-filled n-butyl ferrocene energetic composite combustion rate catalyst, denoted as EF@MnATrtz.
[0046] Example 9
[0047] In this embodiment, equimolar ethyl ferrocene was used to replace catoxine in Example 3, and the other steps were the same as in Example 3, to obtain a brown Mn-EMOFs-filled n-butyl ferrocene energetic composite combustion rate catalyst, denoted as EF@MnDAT.
[0048] Example 10
[0049] In this embodiment, equimolar 1,1'-diethylferrocene was used to replace catoxine in Example 1, and the other steps were the same as in Example 1, to obtain a brown Mn-EMOFs-filled n-butylferrocene energetic composite combustion rate catalyst, denoted as DEF@MnTrtz.
[0050] Example 11
[0051] In this embodiment, equimolar 1,1'-diethylferrocene was used to replace catoxine in Example 2, and the other steps were the same as in Example 2, to obtain a brown Mn-EMOFs-filled n-butylferrocene energetic composite combustion rate catalyst, denoted as DEF@MnATrtz.
[0052] Example 12
[0053] In this embodiment, equimolar 1,1'-diethylferrocene was used to replace catoxine in Example 3, and the other steps were the same as in Example 3, to obtain a brown Mn-EMOFs-filled n-butylferrocene energetic composite combustion rate catalyst, denoted as DEF@MnDAT.
[0054] Comparative Example 1
[0055] 276.3 mg (4 mmol) of 1H-1,2,4-triazole was added to 30 mL of methanol and dissolved by stirring at 25 °C; this solution is recorded as solution A. Then, 361.9 mg (1 mmol) of Mn(ClO4)2·6H2O was added to 30 mL of methanol and dissolved by stirring at 25 °C; this solution is recorded as solution B. Solution A was placed on a magnetic stirrer and stirred at 600 rpm. -1 Solution B was slowly added dropwise to solution A, and the pH of the solution was adjusted to 7-8 with triethylamine. The mixture was stirred at 25°C for 12 hours. After the reaction was complete, the solution was washed with methanol by centrifugation at 10,000 rpm for 3 minutes each time, until the supernatant was completely colorless and transparent. The brown solid precipitate was then dried in a vacuum drying oven at 70°C for 6 hours, ground, and collected to obtain brown Mn-EMOFs, denoted as MnTrtz.
[0056] Comparative Example 2
[0057] In this comparative example, 1H-1,2,4-triazole in Comparative Example 1 was replaced with an equimolar amount of 3-amino-1,2,4-triazole. The other steps were the same as in Comparative Example 1. The resulting brown Mn-EMOFs were denoted as MnATrtz.
[0058] Comparative Example 3
[0059] In this comparative example, 1H-1,2,4-triazole in Comparative Example 1 was replaced with an equimolar amount of 3,5-diamino-1,2,4-triazole. The other steps were the same as in Comparative Example 1. The resulting brown Mn-EMOFs were denoted as MnDAT.
[0060] The combustion catalytic performance of AP was analyzed in the materials obtained in Examples 1-12 and Comparative Examples 1-3, respectively. The results are shown in the figure. Figures 4-7Compared to pure AP, the addition of Mn-EMOFs in Comparative Examples 1–3 or the energetic composite combustion rate catalysts in Examples 1–12 reduced the high-temperature decomposition peak temperature to 292.9–315.7 °C and increased the heat release to 1497.72–1611.21 J·g. -1 The catalysts exhibited good combustion catalytic performance for the thermal decomposition of AP. Comparison of the DSC test curves of AP by ferrocene derivatives revealed that the energetic composite combustion rate catalysts in Examples 1-12 showed higher catalytic effects on AP than the ferrocene derivatives themselves. Not only was the heat of combustion increased to a certain extent, but the decomposition peak temperature also shifted significantly to the left, and the exothermic range became more concentrated. This indicates that the combination of ferrocene derivatives and EMOFs helps to enhance their combustion catalytic activity. Furthermore, Example 4 showed the highest relative catalytic activity, increasing the heat of combustion of AP by approximately 2.37 times (T0). HTD =292.9℃, △H=1611.21J / g).
[0061] In addition, a 24-hour isothermal thermogravimetric analysis (TGA) was conducted on the catotine and the energetic composite combustion rate catalysts prepared in Examples 3, 6, 9, and 12 at 70°C. The test results are as follows: Figure 8 As shown, pure captosine experienced significant weight loss after being kept at 70°C for 24 hours, losing approximately 4.3 wt.% of its mass. Under the same conditions, the weight loss of the energetic composite combustion rate catalysts prepared in Examples 3, 6, 9, and 12 was almost negligible, thus demonstrating that the energetic composite combustion rate catalyst of this invention possesses better anti-volatility properties compared to ferrocene-based combustion rate catalysts. This also indirectly proves that the energetic composite combustion rate catalyst of this invention has excellent anti-migration capabilities. Figure 9 and Figure 10 The figures show the migration resistance test results for catoroxan and the energetic composite combustion rate catalyst prepared in Example 3, respectively, after storage at 50°C for one month. As can be seen from the figures, catoroxan underwent significant migration, migrating by 4.0 mm, 3.1 mm, 2.8 mm, and 1.2 mm in the first, second, third, and fourth weeks, respectively; while the energetic composite combustion rate catalyst prepared in Example 3 showed almost no migration. The results indicate that filling the pores of triazole-based EMOFs materials with ferrocene derivatives can significantly improve the volatility resistance and migration resistance of ferrocene combustion rate catalysts, demonstrating excellent anti-migration and anti-volatilization potential.
Claims
1. A class of triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalysts, characterized in that: The energetic composite combustion rate catalyst is made by filling ferrocene derivatives into the nanopores of an energetic metal-organic framework material with manganese as the metal center and triazole compounds as organic ligands; the mass ratio of ferrocene derivatives to energetic metal-organic framework material in the energetic composite combustion rate catalyst is 0.10 to 0.16:
1. The energetic composite combustion rate catalyst was prepared by the following method: Triazole compounds and ferrocene derivatives were dissolved in a mixed solvent of methanol and acetone to obtain solution A; manganese perchlorate was dissolved in a mixed solvent of methanol and acetone to obtain solution B; then, under stirring, solution B was added dropwise to solution A, and the pH was adjusted to 7-8 with triethylamine. The reaction was stirred at room temperature for 8-12 h. The resulting precipitate was washed with anhydrous diethyl ether by centrifugation until colorless, and then dried under vacuum to obtain a triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalyst. The triazole compound is selected from any one of 1H-1,2,4-triazole, 3-amino-1,2,4-triazole, and 3,5-diamino-1,2,4-triazole; The ferrocene derivative is selected from any one of catoxine, n-butylferrocene, ethylferrocene, and 1,1'-diethylferrocene.
2. The triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalyst according to claim 1, characterized in that: The molar ratio of manganese perchlorate to triazole compounds and ferrocene derivatives is 1:3 to 6:3 to 6.
3. The triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalyst according to claim 1, characterized in that: The volume ratio of methanol to acetone in the mixed solvent is 0.5 to 1.5:
1.
4. The triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalyst according to claim 1, characterized in that: The centrifugation speed is 9000-10000 rpm, and the centrifugation time is 3-4 min.
5. The triazole-based EMOFs-filled ferrocene derivative energetic composite combustion rate catalyst according to claim 1, characterized in that: The vacuum drying temperature is 60–70°C and the time is 6–8 h.
Citation Information
Patent Citations
ZIF-67 filled ferrocene derivative nano-composite burning rate catalyst
CN115582145A
ZIF-67 embedded carbonyl metal composite burning rate catalyst
CN115974631A
Furazan energetic metal complex and preparation method thereof
CN118084875A
